Pergeseran Kompetensi Yurisdiksi antara Pengadilan Agama dan Pengadilan Negeri: Kajian Sosiologi dan Pluralisme Hukum - Ahmad Arif Khoirul Muttaqin; Nur Kholis Majid (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Abstract The jurisdictional competition between the Religious Court and the District Court in sharia economic cases reflects the dynamics of legal pluralism and social change in Indonesia. The duality of norms in regulations, particularly the absolute authority of the Religious Court on the one hand and the opportunity for choice of forum on the other, has led to structural competition between the two judicial institutions in claiming authority over sharia economic disputes. This article analyzes this phenomenon through a legal-normative and sociological approach to explain how the two formal legal systems compete for legitimacy and public trust. The results of the study show that jurisdictional competition is not only caused by regulatory disharmony, but also by the social dynamics of Muslim communities who have different preferences regarding dispute resolution forums. Ultimately, this competition was resolved normatively through a constitutional affirmation that strengthened the position of the Religious Court as the primary authority in sharia economic disputes, while also illustrating the direction of Indonesia's legal pluralism toward a more integrative pattern. Keywords: Religious Court, District Court, Jurisdictional Competition, Legal Pluralism, Sociology of Law.